CHALLANGES AND PROSPECTS IN THE FIELD OF COMMERCE AND MANAGEMENT (International Journal of Food and Nutritional Sciences, 2022)
The field of commerce and management is evolving rapidly due to technological advancements, globalization, and changing consumer preferences. This evolution presents a myriad of challenges and prospects for businesses, educators, and policymakers. Key challenges include adapting to digital transformation, managing global supply chains, and addressing the increasing demand for sustainable and ethical business practices. Additionally, the rise of e-commerce, big data analytics, and artificial intelligence is reshaping traditional business models and strategies, requiring managers and commerce professionals to acquire new skills and knowledge. Conversely, these changes also present significant opportunities for innovation, market expansion, and the development of new business models that leverage digital tools and sustainable practices. This paper aims to explore these challenges and prospects, providing a comprehensive analysis of how businesses can navigate the complex landscape of modern commerce and management. By understanding these dynamics, organizations can better position themselves to capitalize on emerging opportunities while mitigating potential risks.E-commerce, Big Data Analytics.